ANALYSIS OF CRITICAL MINERAL OCCURANCE IN ROCK AND SOIL SAMPLES IN MAMUJU, WEST SULAWESI - Syahwalid, Kokoh
Critical minerals are essential raw materials for the national economy and national defense and security, with the potential for supply disruptions and limited substitutes. Due to these conditions, research on their availability in Indonesia is necessary. Mamuju Regency, West Sulawesi, is one of the areas in Indonesia that has prospects for the availability of critical minerals, especially rare earth elements and radioactive elements. This is indicated by its volcanic rocks, which emit relatively high natural radiation. This research aims to determine the weathering conditions and the availability of rare earth elements and radioactive elements in Mamuju Regency, West Sulawesi. This research was conducted in two locations, namely Tapalang District and Simboro District, with each sample taken from horizons O, A, B, and C. Furthermore, the samples were analyzed using petrography methods, reflectance spectroscopy, SEM-EDS, and XRF to examine the geochemistry of rock weathering and the availability of rare earth elements and radioactive elements in the study area. Petrographiy analysis revealed allanite as the bearing minerals of rare earth elements. Furthermore, the geochemical analysis showed the mobility of major elements and showed a relatively positive correlation between SiO2 and Y2O3 (REE) in each weathering horizon. The lateritization that occurred in both samples was in the weak lateritization zone, indicating that a strong lateritization process had not yet occurred. The critical minerals found in each horizon were Y2O3 and ThO2, which were only found in horizons O, A, and B. SEM-EDS analysis showed the presence of La, Ce, Nd, and Th with high concentrations ranging from 10 wt% to 20 wt% in horizon B.